Risk of febrile seizure after measles–mumps–rubella–varicella vaccine: A systematic review and meta-analysis. Issue 31 (17th July 2015) - Ma, Shu-Juan; Xiong, Yi-Quan; Jiang, Li-Na; Chen, Qing
Highlights We use systematic strategy and broad search terms in multiple databases and websites. We use rigorous methods to extract and appraise the data. Both clinical trials and post-marketing observations are included to analyze. MMRV vaccine increases potential risk of febrile seizure during second observed week. We provide evidence-based knowledge of febrile seizure risk after MMRV vaccine.